Quasi-static and dynamic nanomechanical characterization of PMMA/ZnO nanocomposite thick films synthesized by ultrasonication and spin-coating. Issue 9 (November 2021) - Krishna, B; Chaturvedi, A; Mishra, Neelam; Das, K
Polymer nanocomposite films, comprising of polymethylmethacrylate (PMMA) as the matrix and zinc oxide (ZnO) nanoparticles as reinforcement, have been prepared using ultrasonication and spin-coating techniques, with ZnO content up to 20 wt.%. The effect of the processing on the microstructure and nanomechanical properties have been investigated. The nanocomposite film thickness is found to vary from 2.4 ± 0.2 µm for pristine PMMA to 33.1 ± 0.5 µm for PMMA/20 wt.% ZnO nanocomposite. Quasi-static nanoindentation showed that the indentation modulus varied from 4.68 ± 0.07 GPa for pristine PMMA to 5.04 ± 0.14 GPa for PMMA/20 wt.% ZnO nanocomposite, while the indentation hardness varied from 275.94 ± 5.67 MPa to 292.39 ± 10.88 MPa in the same range. However, the highest indentation modulus and the highest hardness are exhibited by PMMA/10 wt.% ZnO nanocomposite. Scanning electron microscopy of the synthesized films provided the evidence behind such variation in material properties. In addition, the experimentally obtained elastic moduli were compared with values predicted by using Eshelby-Mori-Tanaka micromechanics. Nanoindenter-based dynamic mechanical analysis of the PMMA nanocomposite thin films revealed the variation of storage modulus, loss modulus and loss factor of the films in the frequency range of 10 Hz to 201.5 Hz. For all PMMA/ZnO nanocomposites, the storage modulus is found to increase monotonically from 10 Hz to ∼100 Hz, beyond which the values reached a plateau. The loss modulus and loss factor for all PMMA/ZnO nanocomposites are found to decrease with increasing frequency. These results form an essential step toward establishing process-structure-nanomechanical property relationships for PMMA/ZnO nanocomposite films.